MYC is not detected in highly proliferating normal spermatogonia but is coupled with CIP2A in testicular cancers - Ventelä S; Mäkelä J-A; Sears RC; Toppari J; Westermarck J (My University, 2022)
High MYC expression is linked to proliferative activity in most normal tissues and in cancer. MYC also supports self-renewal and proliferation of many types of tissue progenitor cells. Cancerous inhibitor of PP2A (CIP2A) promotes MYC phosphorylation and activity during intestinal crypt regeneration in vivo and in various cancers. CIP2A also supports male germ cell proliferation in vivo. However, the role of MYC in normal germ cell proliferation and spermatogonial progenitor self-renewal is currently unclear.  Here, we demonstrate that male germ cells are CIP2A-positive but lack detectable levels of MYC protein; whereas MYC is highly expressed in Leydig cells and peritubular myoid cells contributing thereby to the testicular stem cell niche. On the other hand,  MYC was co-expressed with CIP2A in testicular cancers. These results demonstrate that CIP2A and MYC are spatially uncoupled in the regulation of spermatogenesis, but functional relationship between these two human oncoproteins is established during testicular cancer transformation. We propose that further analysis of mechanisms of MYC silencing in spermatogonial progenitors may reveal novel fundamental information relevant to understanding of MYC expression in cancer.